2009
DOI: 10.1051/alr/2009056
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rearing density on sea bass (Dicentrarchus labrax) biological performance, blood parameters and disease resistance in a flow through system

Abstract: -During 84 days, the effects of density on juvenile sea bass (Dicentrarchus labrax) (76 ± 16 g) were studied in an experimental tank-based flow through system. Performance, stress response and resistance to virus infection were analysed under five stabilized rearing densities: 10, 20, 40, 70 and 100 kg m −3 . Water quality parameters (CO 2 , total ammonia nitrogen and O 2 ) were measured and maintained close to the recommended values for farmed sea bass by adjusting water renewal exchange. No significant diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 43 publications
0
17
0
1
Order By: Relevance
“…Feeding the fish once daily does not seem to have effected overall growth in LMB. Similar feeding methods are reported for LMB (Petit et al ) and for feeding other predacious fish such as sea bass, Dicentrarchus labrax (Sammouth et al ; d'Orbcastel et al ).…”
Section: Resultsmentioning
confidence: 60%
“…Feeding the fish once daily does not seem to have effected overall growth in LMB. Similar feeding methods are reported for LMB (Petit et al ) and for feeding other predacious fish such as sea bass, Dicentrarchus labrax (Sammouth et al ; d'Orbcastel et al ).…”
Section: Resultsmentioning
confidence: 60%
“…It was found to decrease in "potential crowding" (Sutton et al 2000); the conditions in this other experiment were different from those in our own, however (modification of the flow rate and water parameters). For the present experiment on density, several hypothesis can be put forward: (i) TSP decrease starts but is compensated by the end of the experiment, as previously observed after TSP decrease due to stress (Coeurdacier and Dutto 1999;El-Gohary et al 2005); (ii) Stocking density has no influence on TSP, but modifies swimming behaviour, affects feed intake, growth and blood pCO 2 and HCO 3 (Sammouth et al 2008;Roque d'Orbcastel et al 2010), as already reported for several blood components in sea bass (Vazzana et al 2002). In similar experimental conditions to the present ones, an effect on the level of gene expression was found (Gornati et al 2004).…”
Section: Discussionmentioning
confidence: 63%
“…Their full details and subsequent results are described in Sammouth et al (2008), Taranger (2008) and Roque d'Orbcastel et al (2010). For the transfer and nodavirus injection treatments, the general conditions of rearing and monitoring are the same.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations